Effect of pH on boron adsorption in some soils of Parana, Brazil - Steiner, Fabio [UNESP]; Lana, Maria do Carmo (Inst Investigaciones Agropecuarias, 2013)
Temporary B deficiency can be triggered by liming of acid soils because of increased B adsorption at higher soil pH. Plants respond directly to the activity of B in soil solution and only indirectly to B adsorbed on soil constituents. Because the range between deficient and toxic B concentration is relatively narrow, this poses difficulty in maintaining appropriate B levels in soil solution. Thus, knowledge of the chemical behavior of B in the soil is particularly important. The present study investigated the effect of soil pH on B adsorption in four soils of Parana State, and to correlate these values with the physical and chemical properties of the soils. Surface samples were taken from a Rhodic Hapludox, Arenic Hapludalf, Arenic Hapludult, and one Typic Usthorthent. To evaluate the effect of pH on B adsorption, subsamples soil received the application of increasing rates of calcium carbonate. Boron adsorption was accomplished by shaking 2.0 g soil, for 24 h, with 20 mL of 0.01 mol L-1 NaCl solution containing different concentrations (0.0, 0.1, 0.2, 0.4, 0.8, 1.2, 1.6, 2.0, and 4.0 mg B L-1). Sorption was fitted to non-linear form of the Langmuir adsorption isotherm. Boron adsorption increased as concentration increased. Boron adsorption was dependent on soil pH, increasing as a function of pH in the range between 4.6 and 7.4, although the bonding energy has decreased. Maximum adsorption capacity (MAC) of B was observed in the Arenic Hapludalf (49.8 mg B kg(-1) soil) followed by Arenic Hapludult (22.5 mg kg(-1)), Rhodic Hapludox (17.4 mg kg(-1)), and Typic Usthorthent (7.0 mg kg(-1)). The organic matter content, clay content, and aluminum oxide content (Al2O3) were the soils properties that affecting the B adsorption on Parana soils.
Keywords: Langmuir isotherm; maximum adsorption capacity; liming; boron fertilizer